Nonsurgical treatments for patients with radicular pain from lumbosacral disc herniation - Lee, Jung Hwan; Choi, Kyoung Hyo; Kang, Seok; Kim, Dong Hwan; Kim, Du Hwan; Kim, Bo Ryun; Kim, Won; Kim, Jung Hwan; Do, Kyung Hee; Do, Jong Geol; Ryu, Ju Seok; Min, Kyunghoon; et al. (The spine journal, 2019)
Lumbosacral disc herniation (LDH) is one of the most frequent musculoskeletal diseases causative of sick leave in the workplace and morbidity in daily activities. Nonsurgical managements are considered as first line treatment before surgical treatment. This clinical practice guideline (CPG) is intended to provide physicians who treat patients diagnosed with LDH with a guideline supported by scientific evidence to assist in decision-making for appropriate and reasonable treatments. A systematic review. Studies of human subjects written in Korean or English that met the following criteria were selected: patients aged ≥18 years, clinical presentation of low back and radicular leg pain, diagnosis of LDH on radiological evaluation including computed tomography or magnetic resonance imaging. Pain and functional evaluation scales such as visual analogue scale, numeric rating scale, and Oswestry disability index The MEDLINE (PubMed), EMBASE, Cochrane Review, and KoreaMed databases were searched for articles regarding non-surgical treatments for LDH published up to July 2017. Of the studies fulfilling these criteria, those investigating clinical results after non-surgical treatment including physical and behavioral therapy, medication, and interventional treatment in terms of pain control and functional improvements were chosen for this study. Nonsurgical treatments were determined to be clinically effective with regards to pain reduction and functional improvement in patients with LDH. Nevertheless, the evidence level was generally not evaluated as high degree, which might be attributed to the paucity of well-designed randomized controlled trials. Exercise and traction were strongly recommended despite moderate level of evidence. Epidural injection was strongly recommended with high degree of evidence and transforaminal approach was more strongly recommended than caudal approach. This CPG provides new and updated evidence-based recommendations for treatment of the patients with LDH, which suggested that, despite an absence of high degrees of evidence level, non-surgical treatments were clinically effective.